(untitled) (World Bulletin of Social Sciences, 2021)
The article discusses the content and essence of import substitution, which is one of the important directions of industrial policy in the country, "import substitution policy" - aimed at stimulating the domestic production and their competitiveness, increasing domestic demand and reducing import demand.